2000
DOI: 10.1111/j.1471-0528.2000.tb11689.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's sexual health after childbirth

Abstract: Objective To investigate the impact of childbirth on the sexual health of primiparous women and idenDesign Setting Population Methods Quantitative analysis of obstetric and survey data.Main outcome measures tify factors associated with dyspareunia.Cross-sectional study using obstetric records, and postal survey six months after delivery.Department of Obstetrics and Gynaecology, St George's Hospital, London.All primiparous women (n = 796) delivered of a live birth in a six month period.Self reported sexual beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
397
13
22

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 442 publications
(468 citation statements)
references
References 44 publications
36
397
13
22
Order By: Relevance
“…Other studies report on dyspareunia as common 6 months after childbirth [3,4]. We found that the number of women with dyspareunia was still high at 12 months postpartum.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Other studies report on dyspareunia as common 6 months after childbirth [3,4]. We found that the number of women with dyspareunia was still high at 12 months postpartum.…”
Section: Discussionsupporting
confidence: 52%
“…The overall impression from published research is that dyspareunia is prevalent in the first 6 months after childbirth and after this period it gradually declines [5]. Associations between pre-pregnancy and postpartum dyspareunia have been found [3,6], but these results are based on retrospective studies.…”
contrasting
confidence: 39%
See 2 more Smart Citations
“…20,21 Other bowel problems such as haemorrhoids 19,22,23 and constipation 24 are more common after IVD, as are perineal pain and dyspareunia. 24,25 Caesarean section has many adverse sequelae, but, with the exception of faecal incontinence, most of these symptoms are less likely to occur in association with this delivery mode. It is therefore important to investigate positive impacts as well as any possible negative impacts of upright positions in the second stage of labour on maternal health outcomes.…”
Section: Scientific Backgroundmentioning
confidence: 99%